Clinical-epidemiological Characterization of Patients with Hypertensive Heart Disease - Milian Carralero Romero; Alián Pérez Marrero; Liliana Espinosa Castro (Universidad de las Ciencias Médicas de Cienfuegos, 2022)
Background: chronic diseases, such as arterial hypertension, currently constitute one of the greatest challenges facing health systems throughout the world. Objective: to clinically and epidemiologically characterize patients with hypertensive heart disease admitted to the Internal Medicine Service of the Guillermo Domínguez López General Teaching Hospital in Las Tunas. Methods: a descriptive and cross-sectional study was carried out in patients admitted with hypertensive heart disease in the Internal Medicine Service of the Guillermo Domínguez López General Teaching Hospital in the municipality of Puerto Padre, Las Tunas province, from June 2019 to June 2021. The universe was made up of all the patients with the diagnosis of said entity. The following variables were included: age, sex, skin color, risk factors, degrees of arterial hypertension, time of evolution of arterial hypertension, types and complications of hypertensive heart disease. Descriptive statistics were used. Results: there was a predominance of male patients (56.6 %) and the age group between 60 and 69 years (35.1 %). Smoking (35.9 %) as the most prevalent risk factor. The correlation between type IV and grade III (15.9 %) predominated. As well as type IV in hypertensive patients with more than thirty years of evolution (42.7 %). Cerebrovascular disease (33.2 %) and heart failure (25.5 %) predominated as complications. Conclusions: it was concluded that male hypertensive patients, over sixty years old and smokers are prone to developing hypertensive heart disease, accompanied by other cardiovascular diseases, as complications.